Ubiquitous Writing, Technologies, and the Social Practice of Literacies of Coordination. (January 2014) - Pigg, Stacey; Grabill, Jeffrey T.; Brunk-Chavez, Beth; Moore, Jessie L.; Rosinski, Paula; Curran, Paul G.
This article shares results from a multi-institutional study of the role of writing in college students' lives. Using case studies built from a larger population survey along with interviews, diaries, and a daily SMS texting protocol, we found that students report SMS texting, lecture notes, and emails to be the most frequent writing practices in college student experience and that these writing practices are often highly valued by students as well. Our data suggest that college students position these pervasive and important writing practices as coordinative acts that create social alignment. Writing to coordinate people and things is more than an instrumental practice: through this activity, college students not only operate within established social collectives that shape literacy but also actively participate in building relationships that support them. In this regard, our study of writing as it functions in everyday use helps us understand contemporary forms of social interaction.